Landlord’s liablity to the power provider for loss of revenue through tampering of electricity meter by the tenant. - Kamarudin, Abdul Rani; Abas, Afridah; Mohamed, Duryana (2019)
Occasionally, if not often than not, the Landlord will by cook or by crook discover that his tenant is guilty of meter tampering to evade paying the prescribed rate amount of his electricity usage to the power provider (licensee). Though meter tampering is an offence, as far as the tenancy agreement is concerned, the tenant may have breached the condition, of if not the warranty of his tenancy agreement with the landlord which may prompt the landlord to terminate the tenancy with the tenant. The question still remains whether the Landlord is liable to the licensee for the unaccounted amount of bill which have been evaded due to the tampering of the electricity meter by the tenant. This article intends to address this issue through analysis of relevant statutory laws and recent decided cases.